2013
DOI: 10.1038/mp.2013.107
|View full text |Cite
|
Sign up to set email alerts
|

A rare mutation of CACNA1C in a patient with bipolar disorder, and decreased gene expression associated with a bipolar-associated common SNP of CACNA1C in brain

Abstract: Timothy Syndrome (TS) is caused by very rare exonic mutations of the CACNA1C gene that produce delayed inactivation of Cav1.2voltage-gated calcium channels during cellular action potentials, with greatly increased influx of calcium into the activated cells. The major clinical feature of this syndrome is a long QT interval that results in cardiac arrhythmias. However, TS also includes cognitive impairment, autism, and major developmental delays in many of the patients. We observed the appearance of Bipolar Diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 41 publications
8
88
0
Order By: Relevance
“…Furthermore, the risk variant is associated with reduced CACNA1C gene expression and transcriptional activity in the eSNP and in vitro experiments, respectively. Another recent study reported that CACNA1C rs1006737 (or rs2159100) is associated with decreased gene expression (Gershon et al, 2013), similar to our findings, although this is not consistently observed (Bigos et al, 2010). Since the initial report of CACNA1C association with bipolar disorder (Ferreira et al, 2008), there has been follow up with studies that report effects on functional connectivity in attention and emotion networks, cognitive performance and personality traits in SCZ and bipolar disorder (Bigos et al, 2010; Erk et al, 2010; Hori et al, 2012; Paulus et al, 2013; Radua et al, 2013; Roussos et al, 2013; Roussos et al, 2011; Tesli et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the risk variant is associated with reduced CACNA1C gene expression and transcriptional activity in the eSNP and in vitro experiments, respectively. Another recent study reported that CACNA1C rs1006737 (or rs2159100) is associated with decreased gene expression (Gershon et al, 2013), similar to our findings, although this is not consistently observed (Bigos et al, 2010). Since the initial report of CACNA1C association with bipolar disorder (Ferreira et al, 2008), there has been follow up with studies that report effects on functional connectivity in attention and emotion networks, cognitive performance and personality traits in SCZ and bipolar disorder (Bigos et al, 2010; Erk et al, 2010; Hori et al, 2012; Paulus et al, 2013; Radua et al, 2013; Roussos et al, 2013; Roussos et al, 2011; Tesli et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…This is, in fact, a well-established theme for Wnt/PCP signaling in other developmental contexts [13,46,47]. A similar phenomenon has been observed for loci contributing to neuropsychiatry through entirely different mechanisms, including ion channel proteins such as KCNA2 for which both gain- and loss-of-function mutations cause epilepsy [48] and CACNA1C for which both a gain-of-function mutation and reduced expression variants are associated with bipolar disorder [49]. This is now also firmly established for several copy number variants, such as 7q11.23 and 22q11.2, that contribute to psychiatric susceptibility either when deleted or duplicated [3,50].…”
Section: Discussionmentioning
confidence: 69%
“…As the SNP is not located in the coding region of the gene CACNA1C , researchers have hypothesized that the variant could influence gene expression. In postmortem brain studies, scientists found evidence of reduced CACNA1C gene expression in individuals with the A allele, particularly in the cerebellum but not in other brain regions 30. However, this finding could not be replicated by other researchers, and some groups have even found increased gene expression 31.…”
Section: Common Variants As Risk Factors For Bipolar Disordermentioning
confidence: 99%